PERAN KOPERASI KONSUMSI PONDOK PESANTREN DALAM PEMBERDAYAAN MASYARAKAT - Julaicha, Siti; Badriyah, Mila (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2022)
Islamic boarding school consumption cooperatives are categorized as sales cooperatives because of buying and selling transactions between the pesantren and their students. The cooperation between the community and pesantren in selling is the result of their production which is collected and traded in the cooperative with a profit-sharing system. This can be a solution in alleviating the poverty of the surrounding community and efforts towards a prosperous and prosperous society, at least it can help the unemployed. This study aims to find out how the role of consumption cooperatives in Islamic boarding schools in an effort to empower the community and to find out what are the supporting and inhibiting factors in their performance. The research method used by the researcher is a descriptive qualitative method in the form of written words from the observed subject. empowerment indicators are access, control, participation, and equality.From the results of this study, it can be seen that the achievement of the consumption cooperative of the Raudlatul Hasanah Islamic boarding school in an effort to improve the economic welfare of the surrounding community in the form of creating jobs, prospering the economy of rural communities and realizing an equal standard of living for the community. The supporting factors are: 1). Enthusiastic students. 2). Society participation. 3). coaching. 4). Very strategic location. 5). availability of housing. While the inhibiting factors, namely: 1). Running out of raw materials. 2). reduced student buying interest. 3). Constrained in permit sales of production out of boarding schools.Â